PERBANDINGAN LINGUISTIK ARAB DAN BARAT: ANALISIS KRITIS TERHADAP SAUSSURE DAN CHOMSKY: Analisis Epistemologis dan Metodologis Linguistik Arab dalam Perspektif Saussure dan Chomsky - Agus Ikhsanudin; Asep Parida; Nurlaela; Iis Susiawati (STKIP Subang, 2025)
This paper presents a critical comparative analysis between classical Arabic linguistics and Western linguistic theories as proposed by Ferdinand de Saussure and Noam Chomsky. The study employs a literature-based qualitative approach to explore conceptual, methodological, and epistemological differences among the three traditions. Classical Arabic linguistics, rooted in the Islamic scholarly tradition of Fiqh al-Lughah, emphasizes the preservation of the Arabic language as the medium of divine revelation. Its system combines normative and descriptive elements through the sciences of nahwu (syntax) and sharaf (morphology), focusing on the triadic word classification of ism, fi‘l, and harf. This framework integrates linguistic, religious, and philosophical dimensions, making Arabic linguistics both rule-based and meaning-oriented. In contrast, Ferdinand de Saussure’s structuralism shifted the focus of linguistic studies from historical to synchronic analysis. His concepts of signifiant and signifié, and the distinction between langue and parole, established the foundation for modern structural linguistics and semiotics. Meanwhile, Noam Chomsky revolutionized the field with his theory of generative-transformational grammar, arguing that language ability is innate through the Language Acquisition Device (LAD). He introduced the notions of linguistic competence and performance, as well as deep and surface structures, emphasizing language as a universal cognitive faculty. The comparative analysis reveals that Arabic linguistics is normative and spiritually grounded, Saussure’s theory is structural and social, while Chomsky’s model is cognitive and universal. Each framework has distinct strengths and limitations, yet integrating their insights provides a comprehensive approach to modern Arabic language education. This synthesis combining the normative foundation of Arabic linguistics, the structural focus of Saussure, and the generative cognition of Chomsky can enhance both theoretical understanding and practical pedagogy of Arabic linguistics in contemporary contexts.